2021
DOI: 10.1017/wet.2021.101
|View full text |Cite
|
Sign up to set email alerts
|

Palmer amaranth (Amaranthus palmeri) interference and seed production in dry edible bean

Abstract: Although Palmer amaranth is currently not widespread in most dry edible bean−producing states in the United States, it is widespread in Western Nebraska, a major dry edible bean−producing region. There is currently a lack of research on management and biology of Palmer amaranth within dry edible bean production. The objective of this study was to quantify the impact of season−long Palmer amaranth interference on yield of dry edible bean and seed production of Palmer amaranth. A field study was conducted in Sco… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
12
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
5

Relationship

4
1

Authors

Journals

citations
Cited by 8 publications
(12 citation statements)
references
References 41 publications
0
12
0
Order By: Relevance
“…Miranda et al. (2022) concluded that the highest seed production of 376,000 seeds per plant was produced when 0.2 Palmer amaranth plants m −1 row of dry bean, and that this number decreased by 12%, 28%, 55%, and 75% when Palmer amaranth density increased to 0.3, 0.5, 1, and 2 plants m −1 row, respectively.…”
Section: Resultsmentioning
confidence: 99%
“…Miranda et al. (2022) concluded that the highest seed production of 376,000 seeds per plant was produced when 0.2 Palmer amaranth plants m −1 row of dry bean, and that this number decreased by 12%, 28%, 55%, and 75% when Palmer amaranth density increased to 0.3, 0.5, 1, and 2 plants m −1 row, respectively.…”
Section: Resultsmentioning
confidence: 99%
“…The highest Palmer amaranth seed production (1,077,650 seed m −2 ) resulted from glufosinate applied alone compared with the nontreated control (939,690 seed m −2 ) (Table 5). Miranda et al (2021) reported that Palmer amaranth seed production per plant decreased as Palmer amaranth density increased, and concluded that the highest seed production (376,000 seed plant −1 ) occurred at the lowest density of 0.2 plants m –1 row, and that it declined by 12%, 28%, 55%, and 75% when density increased to 0.3, 0.5, 1, and 2 plants m –1 row, respectively. Palmer amaranth density in this study was 43 to 149 plants m –2 in the nontreated control compared with 0 to 15, 6 to 30, and 0 to 8 plants m –2 in preemergence-only, early postemergence–only, and preemergence fb late postemergence herbicide programs, respectively (Table 4).…”
Section: Resultsmentioning
confidence: 99%
“…Even when there were few yield differences among treatments containing an herbicide (Table 6), differences in Palmer amaranth biomass can relate to seed production. Previous studies reported a strong positive correlation between Palmer amaranth biomass and seed production, suggesting that as biomass increases, so does seed production (Mahoney et al 2021;Miranda et al 2022;Schwartz et al 2016;Spaunhorst et al 2018;Webster and Grey 2015). Liu et al (2021b) and Norsworthy et al (2016) concluded that lateemerging Palmer amaranth plants have negligible effects on crop yields; however, if those plants are left uncontrolled, even if they are small, they can set seeds into the soil and carry to future issues.…”
Section: Dry Edible Bean Yieldmentioning
confidence: 99%
“…Palmer amaranth interference reduced corn, soybean, and peanut (Arachis hypogaea L.) yield by 91% at 8 plants m −1 row crop (Massinga et al 2001), 68% at 10 plants m −1 row crop (Klingaman and Oliver 1994), and 67% at 5.2 plants m −1 row crop (Burke et al 2007), respectively. Its interference in dry edible bean reduced yield by 77% at 2 plants m −1 row crop and a 5% yield reduction has been estimated to occur at only 4 plants 100 m −2 (Miranda et al 2022).…”
Section: Introductionmentioning
confidence: 99%